A scoping review of the scientific literature on publicly available databases for Complementary and Integrative Medicine (CIM) studies - Omar, Zaliha; Jethani, Pooja; Bell, Megan M; Gopaul, Urvashy; Abu Hassan, Salmah Anim; Chang Dae, Lee; Hsiao-ju, Cheng; Van Rotterdam, Joan; Mohapatra, Bijoyaa; Excell, Laura D.; Heyn, Patricia C.; Kim, Sonya; et al. (International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY), 2022)
Review question / Objective: Review Questions: 1. What are the publicly available databases that can identified in Complementary and Integrative Medicine (CIM) studies? 2. What are the main characteristics of these studies? 3. Which of the CIM studies identified are associated with rehabilitation? Objectives 1. To create a tool for future research approaches based on lessons from the studies identified - hence promoting robust scientific protocols in its pursuit – for better acceptance by scientists, practitioners, and end-users. 2. To map and review open access databases that include CIM related data as defined by the National Institute of Health in 2012. 3. To highlight a subset of CIM studies that are associated with rehabilitation; to be identified as CIRM and promote it as an inclusive rehabilitative modality. 4. To guide future research on Complementary and Integrative Medicine. 5. To stimulate future research in Complementary and Integrative Medicine. 6. To promote evidence-based practice in Complementary and Integrative Medicine.